Experiences of fatherhood in prison: A thematic analysis of differences between fathers in a family approach programme and a comparison group - Venema, Simon D. (European journal of criminology, 2024)
Various programmes have been implemented in prisons to strengthen parental involvement and parent?child relationships during imprisonment. In-depth insights into such programmes are limited. This qualitative study compared the experiences of two groups of imprisoned fathers in the Netherlands: fathers who participated in a family approach programme (N?=?10) and fathers in a comparison group (N?=?29). Based on a thematic analysis, four key differences were identified between the family approach group and the comparison group. Fathers in the family approach group: (1) described more positive engagement activities in direct father?child interactions, (2) reflected more positively on their fathering role during imprisonment, (3) structurally included participation in the family approach programme in their narratives of how imprisonment affected father?child relationship quality, and (4) more often expressed feelings of uncertainty and caution when discussing family life after imprisonment. The findings of this study are informative for the mechanisms behind prison-based parenting and family relationship programmes and illustrate the potential of these programmes to alleviate the unintended negative impact of imprisonment on parental involvement and family relationships. Based on these findings, recommendations for further research and practice are provided.